My Dog is Best - Catrow, David (New York : Holiday House, 2024)
"An easy-to-read book about funny dogs and the kids who love them"--
Keywords: Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Humorous stories; Dogs -- Fiction; Pets -- Fiction; Humorous fiction; Picture books